ANALISIS RASIO AKTIVITAS UNTUK MENILAI KINERJA KEUANGAN PADA PT. XL AXIATA Tbk TAHUN 2015-2019 - Heny Fitriani (Jurnal Akuntansi Indonesia, 2018)
As a cellular telecommunications operator company which is in the second best position in Indonesia and has a market share of around 20%, many competitors can threaten the company's business situation, it is necessary to analyze how the financial performance of PT. XL Axiata Tbk in order to improve the effectiveness and efficiency of the company, in this case the researchers focused on the utilization of company resources. The purpose of this study was to determine how the activity ratio analysis at PT. XL Axiata Tbk listed on the Indonesia Stock Exchange (IDX) in 2015-2019 and to assess how the financial performance of PT. XL Axiata Tbk which was listed on the Indonesia Stock Exchange (IDX) in 2015-2019. The method used in this research is a quantitative descriptive approach, which is research that is then processed and analyzed to draw conclusions. This means that this research emphasizes the analysis of existing data. Overall, the financial performance of PT XL Axiata Tbk is considered not good because it has not been able to produce maximum profits and has not been able to manage its assets efficiently. Keywords: Activity Ratio, Efficiency, Effectiveness, Financial Performance.